Предмет: Алгебра,
автор: Сашуня05
нужно разложить на множители, help please!
Приложения:
Ответы
Автор ответа:
0
Метод группировки:
1 с 3,2 с 4 ..получаем..
(х³+5х)-(3х²+5)=х(х²+5)-3(х²+5)=(х²+5)(х-3)
1 с 3,2 с 4 ..получаем..
(х³+5х)-(3х²+5)=х(х²+5)-3(х²+5)=(х²+5)(х-3)
Автор ответа:
0
Спасибо большое)))
Автор ответа:
0
)))
Похожие вопросы
Предмет: Русский язык,
автор: sonyafrolovaa
Предмет: Русский язык,
автор: Аноним
Предмет: Русский язык,
автор: cerpanovasebine4
Предмет: Геометрия,
автор: Alian98
Предмет: Химия,
автор: supana93